2021
DOI: 10.21037/apm-21-1713
|View full text |Cite
|
Sign up to set email alerts
|

The impact of transthoracic echocardiography on the short-term prognosis of elderly patients in the intensive care unit: a retrospective analysis based on the MIMIC-III database

Abstract: Background: Elderly patients in the intensive care unit (ICU) often suffer from cardiac function impairment. Real-time monitoring of cardiac function and structural changes has important clinical significance. Transthoracic echocardiography (TTE) is a convenient, intuitive, and non-invasive real-time examination of the heart, and it has been widely used for intensive care patients. This study aims to analyze the impact of TTE on the prognosis of elderly patients in ICU.Methods: Data from elderly patients in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Additionally, the maximum dose of norepinephrine in the TTE group was significantly higher than that in the non-TTE group. The results of this study were consistent with those of other studies (16,18). MODS mainly affects the heart, lungs, liver, and kidneys.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the maximum dose of norepinephrine in the TTE group was significantly higher than that in the non-TTE group. The results of this study were consistent with those of other studies (16,18). MODS mainly affects the heart, lungs, liver, and kidneys.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study of patients with AKI in the ICU are consistent with those of the study by Feng et al (11), who focused on sepsis patients in the ICU. Similarly, in another study, Li et al found that performing TTE was associated with decreased 28-day mortality in middleaged and elderly patients in the ICU (16). In fact, all three categories (AKI, sepsis, older) are common patients in ICUs, and there is extensive overlap between the categories (17,18).…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, in the matched cohort, there may have been some patients who should have undergone TTE but did not and this can lead to the clinician not fully understanding the patient’s condition, which is not conducive to the formulation or adjustment of treatment plans. Based on the results of this and similar studies ( 11 , 16 ), for patients with clear indications for a TTE examination, it should be actively considered, and may help reduce the short-term risk of death of patients ( 11 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 91%